Conflitos e integração entre marketing e logística na definição do nível de serviços em vendas e distribuição de produtos: um estudo de caso na indústria de bebidas - Fernandes Júnior, Aldo (2011)
Beverage industries in Brazil are in pursuit of improvements in customer services to fulfill the new marketplace needs, taking into consideration both the change in consumer, habits which now show a preference for healthier goods, and the recent growth in all social economic levels. The services that need more attention are the sales and distribution departments. The former because it is trying to improve the service level to adjust to the new reality, the latter because it faces the challenge of optimizing and properly playing its role in terms of performance and cost effectiveness. Considering that improvements in sales service levels may result in a worse performance and higher distribution costs, conflict between the areas are probable and expected, especially when each one is trying to improve results individually. The service level in sales within the beverage industry could be divided into components, for example: weekly visit frequency, visit duration, weekdays for visiting clients and deadlines for delivering the goods. The primary objective of this study is to verify two hypotheses: (a) whether the manner in which sales functions are organized affects performance and costs in beverage distribution and, (b) in that case, to which degree it quantitatively affects the company s expenses. In other words, to verify that service levels defined by the sales planning team and offered to clients directly reflects the performance and delivery cost for each service level component, with an associated specific cost. Once this cost aggregation is proved, the intention is to analyze and quantify it. In order to validate these hypotheses, a case study is developed in a typical beverage company in Brazil, which has already defined their new service levels without considering its effect on performance and distribution costs. As a consequence of these actions, the studied company had observed a significant rise in these costs and to revert the situation, has considered new alternatives to balance the sales service levels, regarding delivery costs and distribution performance. The company then decided to support the development of a technique known as territory compacting, aiming to improve logistics performance and reduce distribution costs while service levels remain unaffected. Among the precautions adopted to avoid possible service level deterioration, the studied company monitored client perception related to its distribution effectiveness, before and right after the territory compacting was implemented in the most relevantly attended city. Using the technique named Correspondence Analysis, client perception was then rated for various specific sales service levels to avoid damaging the most valued ones for each client. Main operational indicators in sales and distribution are also compared, taking into consideration variations of different periods in cities where territory compacting was applied. Bearing in mind the nature of this study and the participation of the research author, this case study can be sub-classified as action research.